(untitled) (Research, Society and Development, 2025)
This study aims to describe the process of implementing a Standard Operating Procedure (SOP) related to nursing care for patients with the HeartMate III cardiac assist device. This is a descriptive methodological study in which a SOP was developed related to nursing care for patients with the HeartMate III cardiac assist device in a large public hospital specializing in cardiology. It was developed by the Continuing Education Service - Nursing Division after identifying the need to implement and train nursing professionals in relation to care for patients undergoing device implantation. The study indicates that nursing professionals need to have consistent knowledge about the techniques and handling of cardiac assist devices. The development and implementation of this protocol promoted greater safety for users and health professionals, ensuring a reduction in the variability of care actions, improving the qualification of professionals for care decision-making, facilitating the incorporation of new care technologies and thus ensuring greater transparency. Thus, the SOP enters as a management strategy for professionals to ensure the quality of care and the standardization of nursing actions.